A Multicenter Cohort Study of Inferior Vena Cava Filter Use in Children. Issue 12 (23rd July 2015) - Blevins, Erin M.; Glanz, Karen; Huang, Yuan‐Shung V.; Raffini, Leslie; Shinohara, Russell T.; Witmer, Char
<x xml:space="preserve">Abstract</x> Background To describe inferior vena cava (IVC) filter use in pediatric patients admitted to U.S. children's hospitals and to determine factors associated with prophylactic placement. Procedure This retrospective multicenter cohort study utilized data from the Pediatric Health Information Systems (PHIS) administrative database, with 44 participating children's hospitals. Subjects included for analysis were less than 21 years of age, admitted to a PHIS hospital between January 1, 2004 and December 31, 2012 and had a procedure code for IVC filter placement. ICD‐9‐CM discharge codes were used to identify subjects with a venous thromboembolism (VTE). Pharmaceutical billing codes were used to identify anticoagulation use. Results During this 9‐year‐study period, 276 subjects met the inclusion criteria. The median age of subjects was 15 years (range 1 month–20 years). Subjects had an ICD‐9‐CM code for VTE 76% of the time and were started on anticoagulation after IVC filter placement 77% of the time. The mean number of IVC filters placed per year was 6 per 100, 000 admissions (SD‐1.4), which was constant throughout the study period (P = 0.12). The median number of filters placed by center was 4.5 (range 0–32). In multivariate analysis, subjects undergoing orthopedic surgery were more likely to have prophylactic placement of an IVC filter (OR 4.5; 95%CI 1.8‐11). Conclusions IVC filter placement in pediatric patients remains a rare event and is most common in adolescents. Unlike in adults, pediatric IVC filter placement does not appear to be increasing over time and is predominantly used in the setting of a venous thrombotic event. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.